Civilian knowledge industries and the ascendance of small and medium-sized states in world politics - Nir Hassid; Eviatar Matania (Humanities & Social Sciences Communications)
Abstract In the evolving landscape of international politics, the ascent of small and medium-sized (SMS) states in knowledge industries is notable. As these states, exemplified by Israel, Sweden, Singapore, and the United Arab Emirates, harness advanced technological capabilities, their global influence grows. Unlike great powers, SMS states face a heightened risk in developing advanced technology due to limited national resources and the absence of technological redundancies. Our examination of Israel’s experience in the satellite, cybersecurity, and artificial intelligence industries serves as a case study demonstrating how an SMS state can establish competitive knowledge sectors. These technologically advanced SMS states attain a status akin to middle powers, challenging conventional perceptions. Analyzing Israel’s commitment to securing these technological fields reveals government intervention aimed at cultivating sustainable knowledge industries and preserving critical knowledge. While diverse motivations drive the technological development of SMS states, their capabilities reshape conventional notions of middle powers and global power distribution.